Nurse Soft Skills In Community Health Centers (UKM) Services In The Work Area Of The Uptd Puskesmas Inpatient In Lolofitu Moi, West Nias District Year 2020 - Seruan Hati Halawa; Wisnu Hidayat; Taruli Rohana Sinaga (Akupun Tour Publisher, 2023)
Background: The Lolofitu Moi Inpatient Health Center UPTD is one of the Community Health Centers (UKM) in Lolofitu Moi District which has a working area of 4 (four) villages. In addition to services inside the building, the Lolofitu Moi Inpatient Health Center UPTD also provides services outside the building, namely UKM (Community Health Efforts) services. One of the UKM services that is routinely carried out is Posyandu services. In terms of services at Posyandu, the Lolofitu Moi Inpatient Health Center UPTD is inseparable from weaknesses and shortcomings. The community complains about the attitude of nurses who do not respond to patient complaints, sometimes they are not friendly and uncommunicative, the team of nurses in out-of-building services is lacking, they often arrive late at the Posyandu, the confidence of nurses in taking action is still lacking, for example when administering immunization injections some are a bit doubtful, the creativity and independence of nurses' actions at Posyandu also still need to be improved. Purpose: to find out how the Soft Skills of Nurses are in UKM services in the work area of the UPTD Lolofitu Moi Inpatient Health Center. Method: This research is a qualitative research with a grounded research approach. Location The research was conducted at Posyandu in the working area of ​​the UPTD Lolofitu Moi Inpatient Health Center. The research samples were mothers carrying babies immunized at Posyandu, village heads and Posyandu cadres and nurses on duty at Posyandu. Sampling was carried out by means of purposive sampling and the method of data collection was through focused group discussions, in-depth interviews and observation. Results: Nurse's soft skills applied in UKM services in the working area of ​​the Lolofitu Moi Inpatient Health Center UPTD include team work, therapeutic communication, discipline, self confidence, honesty and integrity, strong work ethic, creative and independent. Of the 8 components of nurse soft skills that are applied, team work, honesty and integrity, strong work ethic, creative and independent are the dominant soft skills nurses practice and what has not been done optimally are therapeutic communication, discipline and self confidence Disscusion and Conclusion: The soft skills of nurses in UKM services in the working area of ​​the Lolofitu Moi Inpatient Health Center UPTD that are dominantly practiced are team work, honesty and integrity, strong work ethic, creative and independent. Nurse's soft skills which include therapeutic communication, discipline and self-confidence have not been optimally applied.